Deformation and failure mechanisms of 18650 battery cells under axial compression - Zhu, Juner; Zhang, Xiaowei; Sahraei, Elham; Wierzbicki, Tomasz (Journal of power sources, 2016)
An important deformation mode during ground impacts of battery packs made of cylindrical battery cells is axial compression. This type of loading subjects the cell to a complex deformation pattern and failure mechanism. The design of endcaps plays an important role in such deformations. To explore the sequence of deformation and the underlying failure mechanisms, a combined experimental/numerical study was carried out. Tests were conducted on 18650 cells, and the deformation of each component was carefully investigated and documented. There are four different stages in the force-displacement curve, corresponding with deformation of various components in the endcap assembly. A short circuit happens at a displacement of 4 mm. To clarify these observations, a detailed Finite Element model was set up, covering the geometry and the mechanical property of almost all the components of the cell. Using the simulation results, the sequence of the axial compression was revealed, which was subsequently validated by Micro CT scans as well as analytical solutions. Based on the precise analysis of the mechanical behavior, the cause of the short circuit during axial loading was clarified. Two failure mechanisms in the separator at the top section of the cell explain the possible causes of short circuit. •Short circuit happens when an 18650 battery cell is axially compressed to 4 mm.•Deformation is localized in the positive terminal/endcap region.•Axial compression of jellyroll creates a circumferential crack in the separator in top region.•Deformation of shell casing and jellyroll can be simulated by FE model and explained analytically.